“THE LOGIC OF THE RELATIONSHIP BETWEEN POLITICAL POWER AND PUBLIC SERVICE” (European Journal of Interdisciplinary Research and Development, 2023)
This paper addresses the relationship between political power and public service, the primary common mission of politicians and public officials, short-term and long-term prospects of their goals as well as the distribution of authority, obligations and responsibilities between them. Public officials serve for the benefit of the people. The critical question in this case is: “What is good for the people?”. Should they find the answer to this question on their own? Is it possible to achieve a balance between the political and public-administrative sector? How do the administrative power and the political power relate to each other? Current paper examines these significant questions and sheds some lights on the complicated relationship between political power and public service.